Reaction of endogenous Coenzyme Q10 with nitrogen monoxide and its metabolite nitrogen dioxide - Paola Astolfi; Jean-Louis Clément; Didier Gigmes; Tatiana Armeni; Patricia Carloni; Lucedio Greci (Taylor & Francis Group, 2019)
Objectives: Coenzyme Q10, incorporated in DOPC lyposomes or naturally present in liver bovine mitochondria or in human blood plasma, was reacted with nitrogen dioxide •NO2 or with a •NO/•NO2 mixture. Methods and Results: The reaction course was monitored by Electron Paramagnetic Resonance (EPR) spectroscopy and in all cases the formation of a di-tert-alkyl nitroxide was observed, deriving from the addition of •NO2 to one of the double bonds, most likely the terminal one, of the isoprenic chain. The rate constant for nitroxide formation was also determined by EPR spectroscopy and an initial rate of ca. 7 × 10−8 M s−1 was obtained.